Agriculture, Nutrition, and Gender Linkages (ANGeL) Baseline Study - Ahmed, Akhter; Ghostlaw, Julie; Haque, Md. Latiful; Hossain, Nusrat Z.; Parvin, Aklima; Sufian, Farha D.; Tauseef, Salauddin (International Food Policy Research Institute, 2017)
1.1 Background Bangladesh has made commendable progress in domestic food production through public investments in agricultural research and extension, public and private investments in irrigation, and liberalization of agricultural input markets. In the early 1970s, Bangladesh was a food-deficit country with a population of about 75 million people. Today, the population has more than doubled, and the country is nearly self-sufficient in rice production, which has tripled over the past three decades. However, Bangladesh’s performance in improving child and maternal nutrition has been less satisfactory. Despite its success in reducing child stunting, the rate of stunting in Bangladesh (36 percent in 2014) remains high (NIPORT 2015). Bangladesh also continues to struggle with deficiencies in micronutrients such as iron, zinc, iodine, and vitamin A. Such deficiencies reflect poor diets that are rice-dominated, monotonous, and lacking diversity (Ahmed et al. 2013). Anemia (in part due to iron deficiency) is estimated to affect 26 percent of nonpregnant, non-lactating women, whereas 42 percent suffer from iodine deficiency. About 28 percent women of reproductive age are underweight (NIPORT 2015). In preschool children, the rates of anemia, iodine, and vitamin A deficiencies are 33 percent, 40 percent, and 20 percent, respectively (ICDDR,B 2013). Therefore, government policies and strategies underscore the importance of strengthening the linkage between agriculture and nutrition. Agriculture provides a source of food and nutrients, contributes to income, and affects food prices. Exploring agriculture and nutrition linkages in Bangladesh using data from a multi-round district level panel, a study finds that rice yields are associated with earlier introduction of complementary foods to young children, as well as increases in their weight-for-height (Heady and Hoddinott 2016). Agriculture can also have effects on women’s health, nutrition, empowerment and time allocation, which can have important consequences for their ability to care for family members. Given these links, agriculture has the potential to be a strong driver of nutrition. However, that potential is not being fully realized in Bangladesh because, traditionally, nutrition and agricultural policies have been uncoordinated. Low status of women and gender gaps in health and education contribute to chronic child undernutrition (Smith et al. 2003) and food insecurity (von Grebmer et al. 2009), even when other determinants of food security, such as per capita incomes, improve. According to an IFPRI study, women are key actors within the food system, but are historically disempowered in Bangladesh in terms of leadership in the community, control of resources, and control of income (Sraboni, Quisumbing, and Ahmed 2014a). The lack of women’s empowerment weakens the links between agriculture and nutrition. Despite increases in 2 women’s participation in agriculture in Bangladesh in recent years (Asaduzzaman 2010), women face persistent obstacles, particularly due to social and economic constraints, which limit their further inclusion in agriculture. Women have limited control over agricultural assets, as well as limited mobility to go to markets to sell agricultural produce, often relying on husbands and sons to take produce to market. 1.2 Motivation for the Study IFPRI research in Bangladesh, using data from a nationally representative household survey conducted by IFPRI, reveals that women’s empowerment plays a key role in improving household food security and dietary diversity of children, women, and other household members (Sraboni et al. 2014b; Malapit et al. 2015). The study also shows that agricultural production diversity is associated with dietary diversity (Sraboni et al. 2014b). Further, IFPRI research in Bangladesh shows that nutrition behavior change communication (BCC) training imparted to women and men in rural households leads to significant improvements in child nutrition and complementary feeding practices (Ahmed et al. 2016; Menon et al. 2016). Motivated by research-based evidence, IFPRI researchers developed a concept note to strengthen the agriculture-nutrition-gender nexus in Bangladesh and presented it to the Ministry of Agriculture (MOA), Government of the People’s Republic of Bangladesh in June 2014. Based on the concept note, an inter-ministerial committee of the Government of Bangladesh approved a pilot research project entitled, “Orienting Agriculture Toward Improved Nutrition and Women’s Empowerment”, also known as “Agriculture, Nutrition, and Gender Linkages”(ANGeL), for implementation by the MOA, with technical assistance from IFPRI and Helen Keller International (HKI), and an evaluation led by IFPRI. The Minister of Agriculture officially launched the pilot project in October 2015. The project is jointly funded by the Government of Bangladesh and USAID. 1.3 The Baseline Report As part of the evaluation of the ANGeL Project, IFPRI carried out a baseline survey of project participants and a comparison group of households just before the start of project interventions. This report presents the results of the ANGeL baseline survey. It is organized in nine sections. Section 2 describes the salient features of the ANGeL Project. Section 3 presents the progress of the ANGeL Project to date. Section 4 describes the baseline survey. Section 5 gives a profile of the survey households. Section 6 provides the land tenure status of sample households and findings on agricultural production and practices. Section 7 presents patterns of food consumption and nutrition. Section 8 provides findings on women’s empowerment. Section 9 summarizes the main findings and provides conclusions.